Implementasi Model Project Based Learning (PjBL) dalam Meningkatkan Keterampilan Generik Sains Fisika - Syahidi, Khaerus; Ni'ami, Khairun; Fartina; Zahara, Laxmi; Mardi, Eko Septi (Mataram University, 2024)
This research aims to improve generic science skills by using the Project Based Learning (PjBL) model. This research using the method of classroom action research (PTK) with 2 cycles. Each cycle consists of the stages of planning, implementing actions, observing/observing, and reflecting. The research subjects were class X MIPA 3 of SMAN 3 Selong with a total of 26 people. Data was collected using a test technique to see the increase from cycle 1 to cycle 2. The results showed an increase from cycle 1 to cycle 2 with the percentage of generic science skills from 60.97% to 76.72%, including the medium to high category. The results obtained indicate that there is an increase in generic physics skills by using the Project Based Learning (PjBL) model.